Evaluation of Leaf-Water Relation Traits, as Selection Criterion for Developing Drought Resistant Potato (Solanum Tuberosum L.) Genotypes - Kebede, Zerihun; Mekbib, Firew; Abebe, Tesfaye; Asfaw, Asrat (Review of Plant Studies, 2019)
Though breeding for drought resistance is tricky due to the many physiological and biochemical processes involved and their interaction with the environment; availability of precise, cheap and easy to apply selection tool is critical. The present study quantified the response of potato genotypes to drought and identified potential leaf-water relation traits that enables for identifying drought resistant genotypes. The study assessed sixty genotypes under two irrigation regimes: fully watered non-stress and terminal drought, whereby irrigation was withheld after 50 % flowering to induce post-flowering stress. Measurements for various traits were taken following the potato crop trait ontology. The post-flowering stress induced in this study caused a tuber yield reduction of 33.13% compared with the non-stressed treatment. The genotypes responded differently in tuber yielding potential to the drought. This differential tuber yield response to drought was associated with up and downward regulation of multiple traits related to drought adaptation in potatoes. Drought caused downward regulation on trait responses such as harvest index, leaf area, and specific leaf area. Aboveground biomass and relative water content of leaf contributed negatively for tuber yield under stressed condition. Hence, the attributes identified from this study could help the potato breeding program on drought resistance to develop climate resilient potato varieties.